Climate mobility: Scoping study of two localities in Ghana - Joseph Kofi Teye; Francis Jarawura; Lily Salloum Lindegaard; Nauja Kleist; Marie Ladekjær Gravesen; Philip Mantey; David Quaye (Danish Institute for International Studies (DIIS), 2021)
Climate change is widely expected to produce new and/or intensified mobility patterns, including migration and displacement. However, research on the relationship between climate change and human mobility is limited, especially regarding the role of governance contexts and interventions in shaping mobility responses. The Governing Climate Mobility (GCM) Research Programme seeks to address this gap by examining the relationships between climate change, mobility and governance in Ghana and Ethiopia. This working paper is a scoping study of the programme's case-study areas in the Upper West and Eastern Regions of Ghanaand provides data and analysis on relevant environmental, socio-economic, governance and mobility dynamics. This includes multi-decadal analyses of changes in temperatures, rainfall and vegetation, linking these, and how they are experienced locally, to existing governance and mobility contexts. It builds on a previous GCM working paper on the historical links between climate, mobility and governance in Ghana and identifies key dynamics for further study.
Keywords: 330; Klimawandel; Mobilität; Binnenwanderung; Internationale Migration; Umsiedlung; Entwicklungspolitik; Klimaschutz; Ghana